Family control, R&D expenses and firm efficiency : Evidence from Taiwanese cultural and creative industries - Kweh, Qian Long; Le, Hanh Thi My; Ting, Irene Wei Kiong; Lu, Wen Min (Emerald Publishing, 2023)
Purpose: First, this study assesses the link between research and development (R&D) expenses and firm efficiency. Second, this study explores how family control moderates the link between the two. Design/methodology/approach: This study uses two measures of time-based firm efficiency, namely, a window slacks-based measure (WSBM) and a window epsilon-based measure (WEBM) of data envelopment analysis (DEA). Then, 216 firm-year observations are analyzed in the Taiwanese cultural and creative industries from 2005 to 2017. Findings: This study finds that R&D expenses significantly worsen firm efficiency, and that family control positively moderates this effect. A further test separating the sample into family-controlled and nonfamily-controlled firms indicates that R&D expenses negatively affect the efficiency of nonfamily-controlled firms but positively affect that of family-controlled firms. Research limitations/implications: The existing literature has examined the link between R&D expenses and corporate performance. However, the process by which R&D expenses affect corporate performance from a production perspective remains unknown. Originality/value: Overall, this study provides insights for policymakers to scrutinize resource management and R&D expenses from the production and resource-based perspectives.